Margarita Nelken ou les écritures multiples. Temporalité et engagement - Danièle Bussy Genevois (Cahiers de Civilisation Espagnole Contemporaine)
Margarita Nelken’s notoriety is linked to her multiple functions as a Socialist deputy of the Second Republic. This study offers a different approach by analyzing her writings (feminist, political and literary), in order to better understand how she fits into contemporary history, from the Monarchy to the Spanish Civil War. It is therefore a question of clarifying her cultural and social commitments and of interpreting her successive political loyalties